2023
DOI: 10.1007/s10639-023-11745-1
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a hepatitis-themed virtual escape room in pharmacy education: A pilot study

Abstract: As we enter a world of blended learning in higher education, an increased need for adaptation of teaching strategies to enhance engagement has been recognised to amplify learning outcomes online. Gamification has been identified as a creative tool to engage the current cohort of learners who are also characteristically tech-savvy. To this end, escape room games have gained considerable traction in medical and pharmacy education to promote learning, critical thinking and teamwork. In this pilot study we describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Both lectures and serious games improved post-class test scores to the same level, consistent with previous studies. Krishnan et al found that an educational game on hepatitis significantly improved knowledge scores [ 20 ]. Additionally, our study showed higher knowledge retention in the game group after 6 weeks, in line with previous studies on serious games.…”
Section: Discussionmentioning
confidence: 99%
“…Both lectures and serious games improved post-class test scores to the same level, consistent with previous studies. Krishnan et al found that an educational game on hepatitis significantly improved knowledge scores [ 20 ]. Additionally, our study showed higher knowledge retention in the game group after 6 weeks, in line with previous studies on serious games.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge gain [Aynsley et al, 2018] [Agbo et al, 2021] [Checa et al, 2021] [Ade-Ibijola et al, 2022] [Hsbollah & Rosli, 2022] [Hsbollah & Rosli, 2022] [Krishnan et al, 2023 Enjoyment [Aynsley et al, 2018] [Atmaja et al, 2020] [ Ade-Ibijola et al, 2022] [Krishnan et al, 2023 Educational development [Mercer et al, 2017] [Romero & Kalmpourtzis, 2020 Behavioral change [Mercer et al, 2017][ Ibrahim et al, 2018 Educational tool [Pettit et al, 2015] [Mercer et al, 2017] [Padilla-Zea et al, 2022] [Andrew Tong & Hee, 2023] Better learning outcomes [Nardo & Gaydos, 2021] [Rosa-Castillo et al, 2023 improvement [Pettit et al, 2015] [Pettit et al, 2015] [Hsbollah & Rosli, 2022] [Andrew Tong & Hee, 2023 Motivation improvement [Pettit et al, 2015] [Доброскок et al, 2020] [Frevert & Di Fuccia, 2021] [Agbo et al, 2021] [Wan et al, 2021] [Vodenicharova, 2022][Ade-Ibijola et al, 2022] [Zhyhadlo, 2022] [Andrew Tong & Hee, 2023 Learning effectiveness [Aynsley et al, 2018…”
Section: Benefit Examplesmentioning
confidence: 99%